The Trauma Symptom Checklist for Young Children (TSCYC): reliability and association with abuse exposure in a multi-site study - Briere, John; Johnson, Kerri; Bissada, Angela; Damon, Linda; Crouch, Julie; Gil, Eliana; Hanson, Rochelle; Ernst, Vickie (Child abuse & neglect, 2001)
Objective: The Trauma Symptom Checklist for Young Children (TSCYC) is a 90-item caretaker-report measure of children’s trauma- and abuse-related symptomatology. It contains two reporter validity scales and eight clinical scales [Post-traumatic Stress-Intrusion (PTS-I), Post-traumatic Stress-Avoidance (PTS-AV), Post-traumatic Stress-Arousal (PTS-AR), Post-traumatic Stress-Total (PTS-TOT), Sexual Concerns (SC), Dissociation (DIS), Anxiety (ANX), Depression (DEP), and Anger/Aggression (ANG)], as well as an item assessing hours per week of caretaker contact with the child. This paper introduces the TSCYC and describes its psychometric properties in a multisite validity study. Method: A total of 219 TSCYCs administered by six clinician/researchers across the United States were analyzed for scale reliability and association with several types of childhood maltreatment. Results: The TSCYC clinical scales have good reliability and are associated with exposure to childhood sexual abuse, physical abuse, and witnessing domestic violence. The PTS-I, PTS-AV, PTS-AR, and PTS-TOT scales were most predictive, followed by SC in the case of sexual abuse and DIS in the case of physical abuse. There were a small number of age, sex, and race effects on TSCYC scores. Conclusions: The TSCYC appears to have reasonable psychometric characteristics, and correlates as expected with various types of trauma exposure. Subject to continued validation and the development of general population norms, its use as a clinical measure is supported. Objectif: Le Trauma Symptom Checklist for Young Children (TSCYC) mesure grâce à une enquête remplie par la personne chargée d’un enfant la symptomatologie liée au traumatisme et aux sévices. Elle comporte deux échelles de validité concernant l’expert et 8 échelles cliniques (stress post-traumatique-intrusion (PTS-I), stress post-traumatique-évitement (PTS-AV), stress-post-traumatique-début (PTS-AR), stress post-traumatique-total (PTS-TOT), intérêts sexuels (SC), dissociation (DIS), anxiété ANX), dépression (DEP) et colère-agressivité (ANG), ainsi qu’une évaluation en heures passées pae semaine par l’adulte concerné avec l’enfant. Cet article présente le TSCYC et décrit ses propriétés psychométriques dans une étude de validité à plusieurs emplacements. Méthode: Au total, 219 TSCYC ont été administrés par six cliniciens-chercheurs dans l’ensembles des Etats-Unis et analysés selon la fiabilité et l’association avec différents types de mauvais traitements. Résultats: Les échelles TSCYC ont une bonne fiabilité et sont associées à l’exposition à des sévices physiques et sexuels et au fait d’être témoin de la violence domestique. Les échelles PTS-I, PTS-AV, PTS-AR, et PTS-TOT offrent la meilleure prédiction, suivies par SC dans le cas des sévices sexuels et DIS dans le cas des sévices physiques. Il y a un petit nombre d’effets concernant l’âge, le sexe et la race sur les scores du TSCYC. Conclusions:Le TSCYC semble posséder des caractéristiques psychométriques raisonnables. Il est en corrélation, comme on s’y attendait, avec l’exposition à des traumatismes variés. Ceci est en faveur de son utilisation en tant que mesure clinique s’il est soumis à une validation continue et au développement de normes pour la population générale. Objetivo: El Trauma Symptom Checklist for Young Children (TSCYC) es una medida de informe cumplimentada por el cuidador y compuesta por 90 items que evalúa la sintomatologı́a relacionada con el maltrato y el trauma infantil. Contiene dos escalas de validez y ocho escalas clı́nicas (Estrés Postraumático-Intrusión [PTS-I], Estrés Postraumático-Evitación [PTS-AV], Estrés Postraumático-Activación [PTS-AR], Estrés Postraumático-Total [PTS-TOT], Preocupación Sexual [SC], Disociación [DIS], Ansiedad [ANX], Depresión [DEP], e Ira/Agresión [ANG], ası́ como un item que valora el número de horas por semana que el cuidador tiene contacto con el/la niño/a. Este artı́culo presenta el TSCYC y describe sus propiedades psicométricas en un estudio de validez aplicado varios lugares. Método: Un total de 219 TSCYCs, administrados por seis médicos/investigadores a lo largo de Estados Unidos, fueron analizados para conocer la fiabilidad de la escala y su asociación con diferentes tipos de maltrato infantil. Resultados: La escalas clı́nicas TSCYC tienen una buena fiabilidad y están asociadas con la exposición del niño al abuso sexual, al maltrato fı́sico, y a ser testigo de violencia doméstica. Las escalas PTS-I, PTS-AV, PTS-AR, y PTS-TOT fueron las más predictivas seguidas por el SC en el caso del abuso sexual y por el DIS en el caso de maltrato fı́sico. Hubo un número pequeño de efectos de edad, sexo y raza en puntuaciones de TSCYC.